The first Middle Ordovician and Gondwanan record of the cincinnaticrinid crinoid Ohiocrinus byeongseoni n. sp. from South Korea: biostratigraphy, paleobiogeography, and taphonomy. (July 2022) - Park, Hyeonmin; Lee, Seung-Bae; Woo, Jusun; Lee, Dong-Chan
Abstract: Ohiocrinus byeongseoni n. sp. from the Middle Ordovician (Darriwilian) Jigunsan Formation of South Korea in the Sino-Korean (North China) block is the oldest species of Ohiocrinus of the Cincinnaticrinidae and the first record outside Laurentia. O . byeongseoni is characterized by a loosely clockwise-coiled anal sac, isotomous branching throughout arms, long, slender xenomorphic column, and small lichenocrinid-type holdfast. The new species occurs in association with a deep-water siliciclastic environment, unlike the Laurentian species with a shallow-water carbonate environment. The monospecific crinoid assemblage is interpreted as parautochthonous, considering that the crinoids were reworked by relatively weak down-current probably caused by storm but preserved within the environment where they lived. The occurrence of O . byeongseoni presents a considerable spatiotemporal gap and ecologic disparity in evolution of Ohiocrinus and the Cincinnaticrinidae. UUID: http://zoobank.org/240417a4-8d33-4f45-aedb-afcc07f1ecbb